(untitled) (CIPEEX, 2025)
Self-medication is a widespread practice among medical students, influenced by various demographic factors such as age and gender. This study aimed to demonstrate whether the age and gender of medical students impact the practice of self-medication. This is a systematic review of the literature covering the period from 2018 to 2023, including articles in Portuguese and English, excluding all studies that used secondary data and data prior to 2018. The findings suggest that self-medication is more frequent among female students and younger students, which may reflect variations in risk perceptions and motivations for medication use. Awareness of the potential risks associated with self-medication, as well as specific educational interventions, are essential to reduce this practice. In this context, higher education institutions play a key role in training future doctors who are aware of the risks involved in self-medication, offering resources and support to promote safe and responsible health practices.